Mosaic HIV-1 Vaccines Expand the Breadth and Depth of Cellular Immune Responses in Rhesus Monkeys - Barouch, Dan H. (2010)
The worldwide diversity of HIV-1 presents an unprecedented challenge for vaccine development 1-2. Antigens derived from natural HIV-1 sequences have elicited only limited breadth of cellular immune responses in nonhuman primate studies and clinical trials to date. Polyvalent “mosaic” antigens, in contrast, are designed to optimize cellular immunologic coverage of global HIV-1 sequence diversity 3. Here we show that mosaic HIV-1 Gag, Pol, and Env antigens expressed by recombinant, replication-incompetent adenovirus serotype 26 vectors markedly augmented both the breadth and depth without compromising the magnitude of antigen-specific T lymphocyte responses as compared with consensus or natural sequence HIV-1 antigens in rhesus monkeys. Polyvalent mosaic antigens therefore represent a promising strategy to expand cellular immunologic vaccine coverage for genetically diverse pathogens such as HIV-1.